2006
DOI: 10.1038/modpathol.3800605
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pathologist experience on liver transplant biopsy interpretation

Abstract: We studied the impact of pathologist experience on liver transplant biopsy interpretation for cases designated 'nonspecific' by pathologists at a nontransplant center. Among 102 consecutive liver transplant biopsies from 92 patients performed at the Foothills Medical Center, 30 liver biopsies from 23 patients were designated 'nonspecific' by the local pathologist. These biopsy slides were independently reviewed by an expert in liver transplant pathology at a major US transplant center. The expert pathologist w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…These methods are highly time-consuming and subjective; furthermore, accuracy is heavily dependent on the expertise of the pathologist [24]. In this study, we present a novel approach for automated detection of early cancer in tissue based on simultaneous quantification of mitochondrial organization, cellular morphology, metabolic activity, and keratin localization from non-invasively acquired TPEF images.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are highly time-consuming and subjective; furthermore, accuracy is heavily dependent on the expertise of the pathologist [24]. In this study, we present a novel approach for automated detection of early cancer in tissue based on simultaneous quantification of mitochondrial organization, cellular morphology, metabolic activity, and keratin localization from non-invasively acquired TPEF images.…”
Section: Discussionmentioning
confidence: 99%
“…5,[10][11][12][13][14][15] Several of these factors contribute to establishing a precise diagnosis, but the pathologist's knowledge and experience remain the essential factors in interpretive diagnosis. Although numerous studies have shown that case reviews help detect interpretive diagnostic errors, there have been no efforts to formalize this practice as a strategy to reduce errors.…”
mentioning
confidence: 99%
“…The value of special expertise in interpreting liver transplant biopsy pathology was pointed up in a study which showed that 'expert' review of specimens originally designated as 'nonspecific' at a nontransplant center resulted in revised diagnoses in 27% of cases [61 ]. Conditions that were missed in this setting included early recurrent chronic hepatitis, the fibrosing cholestatic hepatitis variant of recurrent hepatitis C, nodular regenerative hyperplasia, and de-novo autoimmune hepatitis.…”
Section: Liver Transplantation and Graft Versus Host Diseasementioning
confidence: 98%